2010
DOI: 10.3109/00365520903443852
|View full text |Cite
|
Sign up to set email alerts
|

Serum chemerin and vaspin in non-alcoholic fatty liver disease

Abstract: This study shows for the first time that chemerin and vaspin serum concentrations are altered in patients with NAFLD. The analyzed adipokines appear to play a pivotal role in the pathogenesis of NAFLD, not only as regulators of insulin sensitivity, but also as mediators of the inflammatory process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
80
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 26 publications
13
80
5
Order By: Relevance
“…Similar results were obtained by our group in NAFLD patients [22]. Up-regulation of vaspin in patients with marked fibrosis could be a compensatory mechanism having a protective effect directed against further liver injury and fibrosis progression.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar results were obtained by our group in NAFLD patients [22]. Up-regulation of vaspin in patients with marked fibrosis could be a compensatory mechanism having a protective effect directed against further liver injury and fibrosis progression.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, vaspin levels were up-regulated in non-alcoholic steatohepatitis as compared to simple steatosis and paralleled disturbances in HOMA-IR [22]. Since recently CHC has been recognized not only as viral but also as a metabolic disease similar to NAFLD, an interesting finding of our study was a positive relationship between the vaspin level and grade of steatosis in CHC patients.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…After stepwise linear regression analysis, serum vaspin concentration was the only independent predictor of liver fibrosis in patients with NAFLD. Serum vaspin levels were up-regulated in NAFLD patients regardless of potentialconfounders [27].Ourpreviousstudyandthe studybyGencet aldidnotfindanyrelationshipbetweenserumvaspinandfibrosisstageinnon-severely obeseNAFLDpatients [25,26].However,ourstudy in CHC patients showed vaspin serum levels to be significantly higher in patients with significant and advanced fibrosis. Nonetheless, in patients without fibrosis and with insignificant fibrosis vaspin serum levels were significantly lower.…”
Section: Discussioncontrasting
confidence: 46%
“…In humans liver chemerin mRNA positively correlates with NAFLD activity score, and is induced in patients with NASH [9,28]. Serum chemerin is found increased and unchanged in human NASH, and elevated levels are partly associated with higher BMI of the NAFLD patients [9,[28][29][30].…”
mentioning
confidence: 98%